The Role of Caspase Activity and Apoptosis in Nasopharyngeal Carcinoma - Mohd Aminudin, Mustapha; Sim, Sai Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2024)
Objective: To determine roles of caspase activity and apoptosis in nasopharyngeal carcinoma development. Method: Review the article related to caspase activity, apoptosis, and nasopharyngeal carcinoma. Results: Caspase activity and apoptosis suggested to be one of the mechanisms underlying the chromosomal rearrangements in nasopharyngeal carcinoma. Conclusion: Caspase activity and apoptosis may be led to nasopharyngeal carcinoma development.